2022
DOI: 10.17219/acem/151911
|View full text |Cite
|
Sign up to set email alerts
|

Gene network analysis of the transcriptome impact of methylated microRNAs on oral squamous cell carcinoma

Abstract: Background. Oral squamous cell carcinoma (OSCC) is one of the most common head and neck squamous cell tumors. MicroRNAs and DNA methylation, as epigenetic mechanisms, regulate the expression of oncogenes and tumor suppressor genes, contributing to the carcinogenic development. However, the current knowledge on the genetic and epigenetic landscape of OSCC is still limited.Objectives. To assess the transcriptomic impact of microRNAs found to be methylated through Infinium genome-wide methylation profiling of arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Several recent studies highlight the importance of another epigenetic mechanism of gene expression regulation, namely DNA methyla-tion. Avram et al [21] evaluated the impact of the differentially methylated microRNAs in the OSCC transcriptome. They concluded that in contrast to the general decrease in DNA methylation across the entire genome in OSCC, mi-croRNA loci may exhibit an increase in their methylation status.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies highlight the importance of another epigenetic mechanism of gene expression regulation, namely DNA methyla-tion. Avram et al [21] evaluated the impact of the differentially methylated microRNAs in the OSCC transcriptome. They concluded that in contrast to the general decrease in DNA methylation across the entire genome in OSCC, mi-croRNA loci may exhibit an increase in their methylation status.…”
Section: Resultsmentioning
confidence: 99%
“…HPV’s carcinogenic potential is driven by its E6 and E7 oncoproteins [ 21 , 23 , 24 , 25 ]. These proteins provoke uncontrolled cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The action mechanism of miRNA is based on binding to the 3′-UTR of mRNAs and silencing them [ 12 , 13 ]. These types of RNA are involved in the post-transcriptional regulation of approximately 60% of human genes [ 14 ]. miRNAs play an important role in modulating processes such as embryogenesis, cellular development, cell proliferation, cell metabolism, and homeostasis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%